STUDENT CHARACTER GUIDANCE: THROUGH THE PORTOFOLIO PROGRAM FOR THE ROAD WORKSHOP IN THE FITK UIN NORTH SUMATERA MEDAN - Mardianto, Mardianto (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Students are a generation group that has the opportunity to build and develop good character. Fostering the development and development of student characters can be done by lecturers in various ways such as by integrating curriculum and learning strategies and most important is the example or role model. In the subject of Educational Psychology from four classes in the Faculty of Tarbiyah and Teacher Training UIN North Sumatra Medan, character building is done by integrating the coaching 7 (seven) minutes pre lecture. Methodology This research is a qualitative participatory research with the population and sample set directly four classes of students who follow lectures on even semester of 2016/2017. Results obtained, first; students when done through the guidance model by the lecturers will give a positive response to the characters they build. Second; 88,32% of students did not object to the transfer of values from the character portfolio to the value rubric set by UIN Sumatera Utara Medan. Third: The character of students associated with regular worship that is; read Al-Qur`an, to prayer his mother and his father, as well as dawn prayers in congregation in the mosque for men increased from 11,77% to 76,47% at the end of the semester. And this research recommends that to foster student character can be done with exemplary lecturer in worship.